Characterization of Boron-Modified Activated Carbons - Orhan, Ayhan; Cek, Nurettin; Sezer, Selman; Demir, Ismail (Mdpi, 2025)
Although there are various boron production methods for modified activated carbons used in sulfur removal, catalyst synthesis, and hydrogen capture/storage processes, the modification of activated carbon with borax solutions has attracted attention as the easiest synthesis method. However, structural characterization analyses in previous studies contradict each other and, therefore, more detailed characterization is needed. In this study, 0.25 M and 0.5 M borax solutions are prepared in distilled water; then, 2 g of commercial activated carbon is added to each one, mixed at 60 degrees C, filtered, and dried. Thus, two different boron-modified activated carbon materials are obtained. Structural characterization tests of these materials are performed and analyzed by comparing with the literature. As a result, two different boron-modified activated carbon structural analyzes are compared and it is confirmed that commercially activated carbon material induced phase composition and chemical bond modification as a result of modification with borax. It is revealed that the induction of phase composition and chemical bond modification is more dominant with increasing borax concentration. The produced boron-modified activated carbon materials have great promise for the development of new technologies in the fields of the environment, energy, lightweight compressible materials, thermal insulation, and composite materials.
Keywords: carbon materials; commercial activated carbon; borax; boron; modification